Targeting Drug Delivery to the Lungs by Inhalation - C. O'Callaghan (Mediators of Inflammation)
Most drugs targeted to the respiratory tract are used for their local action. For example, ephidrine for nasal decongestion, beta-2 agonists for bronchodilatation, and inhaled steroids to suppress the inflammation seen in asthmatic airways. Since the drug is delivered directly to its required site, only a small quantity is needed for an adequate therapeutic response, and consequently there is a low incidence of systemic side effects compared with oral or intravenous administration. More recently, it has become apparent that the lining of the respiratory tract, from nasal mucosa to airways and alveoli, may be used for the absorption of a drug for its systemic effect. This route of administration may be particularly attractive if it avoids the metabolic destruction encountered when some drugs are administered by alternative routes (for instance, peptides and proteins are rapidly destroyed by peptidases when Oven by the oral route). If there is a lack ofclinical response to an aerosolized drug, it is important to question whether the drug has failed or whether delivery to the site of action is inadequate. To deliver therapeutic agents by inhalation to the lower respiratory tract, inhaled drug particles must have appropriate aerodynamic characteristics. In addition, the anatomy and pathophysiology of the patient's respiratory tract, mode of inhalation through the inhaler, and the characteristics of the inhalational device itself, may significantly affect drug deposition.